Community assembly mechanism of phytoplankton in drinking water sources of tropical island, China - Liu, Xiaojin; Liu, Qi; Chen, Bo; Jiang, Xiaodie; Atif, Sial; Yongo, Edwine; Fu, Qiongyao; Guo, Zhiqiang; Zhu, Weiju (Frontiers in Ecology and Evolution, 2026)
IntroductionPhytoplankton, as primary producers in aquatic ecosystems, serves as indicators of the health of water environments. In tropical island regions facing the combined pressures of human activities and climate change, understanding the mechanism underlying the phytoplankton community structure is crucial. This knowledge is essential for safeguarding drinking water sources and for identifying potential ecological risks in aquatic systems.MethodsThis study focused on 22 drinking water sources on Hainan Island, comprising 11 rivers and 11 reservoirs. Phytoplankton samples were collected during December 2023 (dry season) and July 2024 (wet season). We systematically analyzed the α and β diversity, explored the environmental factors influencing community changes, and examined the mechanism underlying the assembly of the phytoplankton community. Results and discussionThe results revealed a clear seasonal succession in the composition of the dominant phytoplankton community. During the dry season, Cyanophyta, Chlorophyta, and Bacillariophyta were dominant, whereas in the wet season, Cyanophyta dominated. Phytoplankton α-diversity was consistently higher in rivers than in reservoirs and β-diversity was predominantly structured by species turnover (>84%). The Mantel test identified water temperature, pH and total phosphorus as key environmental factors influencing changes in the phytoplankton community structure. Co-occurrence network analysis revealed that during the wet season, the phytoplankton community nodes exhibited higher connection density and stronger correlations. The assembly of these community was primarily governed by dispersal mechanism, with niche processes playing a comparatively minor role. This study provides a novel, mechanistic framework for understanding tropical island aquatic ecosystems, offering critical insights for predicting ecological risks and guiding resilience-based water quality management in the tropical aera.